2018–2019 Florida Citrus Production Guide: Quick Reference Guide to the Worker Protection Standard (WPS) - Michael E. Rogers (EDIS)
This 8-page fact sheet is part of the 2018–2019 Florida Citrus Production Guide. It discusses the Worker Protection Standard (WPS), a regulation originally issued by the US Environmental Protection Agency (EPA) in 1992 and most recently revised in 2015. Written by M.E. Rogers and published by the Entomology and Nematology Department, January 2019.